What kind of Thai Patients factors to Request Prescribing from Physicians - Kobjaiklang, Chulaporn N (Archives of Business Research, 2015)
ABSTRACT This study investigates the Thai healthcare system in regard to the factors influencing the practice of prescribing in the pharmaceutical industry. The healthcare system in Thailand is shifting towards one in which informed patients make their own medical decisions. The sudden increase of channels directed to both patients and medical practitioners makes it very difficult for pharmaceutical companies to control the value of information related to the practice of prescribing. Accordingly, the purpose of this study was to examine the influence of patients influencing factors several marketing channels and their influence on the practice of prescribing. The findings of the study indicated that the study is useful in understanding the variables that influence prescription patterns of patients in the Thai healthcare system. The patients, there was no significant correlation between the patients’ experience with the medication and their intent to request the same medication. Understanding the marketing channels and their relationship with prescribing practices has implications for the development of marketing strategies in the pharmaceutical industry. Keywords: Thai healthcare, prescribing, pharmaceutical industry, patients